2014
DOI: 10.1002/ejoc.201402078
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stereoselective aza‐Baylis–Hillman Reactions of CF3‐Sulfinylimines: Straightforward Access to α‐Methylene β‐CF3 β‐Amino Acids

Abstract: 1,4‐Diazabicyclo[2.2.2]octane‐catalyzed asymmetric aza‐Baylis–Hillman (ABH) reaction of (R)‐N‐tert‐butanesulfinyl‐(3,3,3)‐trifluoroacetaldimine with various Michael acceptors proceeds with exceptionally high rates and stereochemical outcome. This ABH approach provides convenient and practical access to previously unknown enantiomerically pure α‐methylene β‐CF3 β‐amino esters/acids, forthright useable for peptide synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Furthermore, the only stereoselective approaches reported in literature on the synthesis of trifluoromethyl containing six‐membered‐ring α‐amino acids, deal with preparation of some derivatives of pipecolic acid , . Taking into account the ever‐growing importance of fluorinated compounds and our ongoing interest in the development of fluorinated tailor‐made amino acids, we were interested in the development of suitable approaches for the preparation of enantiomerically pure trifluoromethylated analogues of β‐proline and (iso)nipecotic acid. According to Scheme , we envisaged the synthesis of the target molecules from N ‐ tert ‐butanesulfinyl‐(3,3,3)‐trifluoroacetaldimine 1 , which is a very useful starting material for the stereoselective synthesis of fluorinated amino acids …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the only stereoselective approaches reported in literature on the synthesis of trifluoromethyl containing six‐membered‐ring α‐amino acids, deal with preparation of some derivatives of pipecolic acid , . Taking into account the ever‐growing importance of fluorinated compounds and our ongoing interest in the development of fluorinated tailor‐made amino acids, we were interested in the development of suitable approaches for the preparation of enantiomerically pure trifluoromethylated analogues of β‐proline and (iso)nipecotic acid. According to Scheme , we envisaged the synthesis of the target molecules from N ‐ tert ‐butanesulfinyl‐(3,3,3)‐trifluoroacetaldimine 1 , which is a very useful starting material for the stereoselective synthesis of fluorinated amino acids …”
Section: Introductionmentioning
confidence: 99%
“…The reactions between Michael acceptors 112 and imine ( R s )‐ 7 were performed under commonly applied conditions, at ambient temperature and with DABCO as a catalyst. The authors noted that the observed diastereoselectivity, reaction rates, and levels of asymmetric induction were all strikingly better than those achieved with the fluorine‐free analogues. Thus, the reactions were complete in about 1 h with only 10 mol‐% of the catalyst.…”
Section: Reactivity Of (Ss)‐n‐tert‐butylsulfinyl‐333‐trifluoroacmentioning
confidence: 98%
“…It provides straightforward access to β‐amino‐carbonyl compounds through a sequence of addition/elimination processes . Examples of ABH reactions of imine 7 are presented in Scheme …”
Section: Reactivity Of (Ss)‐n‐tert‐butylsulfinyl‐333‐trifluoroacmentioning
confidence: 99%
“…β-Amino α-methylene β-trifluoromethyl carbonyl compounds 93, as new constrained building blocks for incorporation into foldamers, were synthesized by Milcent and co-workers 74 The absolute configuration of the newly formed stereogenic center of major diastereoisomers was assigned by X-ray crystallographic analysis, according to a non-chelated transition state, in contrast to what observed starting from unfluorinated aldimines. In fact on the latter, the addition occurs via a chelated transition state with low reaction rates and moderate stereoselectivity.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%